Inclusion of average rainfall in genetic evaluation of SA Holsteins to mitigate genotype by environment interaction - (:unkn) unknown (My University, 2022)
Genetic improvement for persistency of milk production in South African Holstein cattle in a total mixed ration or pasture production system will be impeded because of the existence of genotype by environment interaction between the production systems. Previous studies where herds’ production system were known (unlike reality) showed that rainfall level indicate the production system preferred by producers. The study aimed to determine the effect of including average rainfall in a random regression model as a possible proxy for production system used. The animal-additive-genetic effect due to annual rainfall (class) was added to the existing additive-genetic-average-production and -persistency effect. Heritability estimates of rainfall class 1 (“low” rainfall) coincided with total mixed ration estimates while rainfall class 5 (“high” rainfall) coincided with pasture estimates in later lactations. Results suggest that genetic background responsible for average production level and persistency over the lactations are not consistent over different rainfall areas.
Keywords: African Research